Sewage Disposal at Point Barrow, Alaska. - Boyd,William L.; Klubek,Brian P.; Boyd,Josephine W. (1972)
A study of the Middle Salt Lagoon, Point Barrow, Alaska, the sewage depository of the Naval Arctic Research Laboratory, was initiated. Microbial analyses were carried out on runoff, lagoon water, and bottom sediments throughout the summer. The lagoon as an incomplete ecosystem is discussed, and the dynamic changes that take place throughout the season are analyzed. (Author)